2016
DOI: 10.1016/j.ijscr.2016.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Replaced gastroduodenal artery: Added benefit of the “artery first” approach during pancreaticoduodenectomy—A case report

Abstract: HighlightsA “replaced” artery is a totally replaced variant artery in the absence of the normal artery that has the same name.The gastroduodenal artery supplies arterial perfusion to the head of the pancreas.Arterial anomalies need to be identified and managed appropriately during surgery to prevent end organ ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…An entirely replaced LHA on a GDA replaced to the SMA is described in 1 case report by Younan et al, however the patient described here is of added interest due to the incongruity with the previously published anatomical model described above (Younan et al 2016). An entire LHA arising from the GDA conforms with Song’s anatomical model.…”
Section: Discussionmentioning
confidence: 69%
“…An entirely replaced LHA on a GDA replaced to the SMA is described in 1 case report by Younan et al, however the patient described here is of added interest due to the incongruity with the previously published anatomical model described above (Younan et al 2016). An entire LHA arising from the GDA conforms with Song’s anatomical model.…”
Section: Discussionmentioning
confidence: 69%
“…In a meta-analysis of CA variations which included 12,000 cases from 36 studies, there was no mention of a replaced GDA (rGDA) [2,7]. Many other studies have identified frequency of variations in origin of rGDA, summarised in Table 1 [14][15][16][17][18][19][20][21][22][23][24][25][26]. The various sites of origin of rGDA are shown in Figure 1.…”
Section: Origin Of Gdamentioning
confidence: 99%
“…Below D1, GDA travels between duodenum and pancreas in the duodenal gutter of Wiart . Studies have shown that a rGDA originating from SMA arises below the neck of the pancreas and runs anterior to the neck of pancreas, whereas a rGDA originating from a rCHA from SMA arises below the neck of pancreas and courses posteriorly or sometimes even through the pancreatic parenchyma and very rarely anterior to the pancreas .…”
Section: Course and Relations Of Gdamentioning
confidence: 99%
See 2 more Smart Citations